2007
DOI: 10.1002/mrd.20839
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate‐Induced phosphorylation of p270 protein in mouse sperm by cAMP‐Dependent protein kinase

Abstract: Signaling by cAMP-dependent protein kinase (PKA) plays an important role in the regulation of mammalian sperm motility. However, it has not been determined how PKA signaling leads to changes in motility, and specific proteins responsible for these changes have not yet been identified as PKA substrates. Anti-phospho-(Ser/Thr) PKA substrate antibodies detected a sperm protein with a relative molecular weight of 270,000 (p270), which was phosphorylated within 1 min after incubation in a medium supporting capacita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…Kiyoshi Miki et al observed a 270 kDa band on a Western blot of post-capacitation spermatozoa lysates using anti-phospho-(Ser/Thr) PKA substrate antibody; however, they did not identify the protein (16). In the present study, we confirmed the presence of a 270 kDa protein band in post-capacitation spermatozoa lysates.…”
Section: +supporting
confidence: 76%
“…Kiyoshi Miki et al observed a 270 kDa band on a Western blot of post-capacitation spermatozoa lysates using anti-phospho-(Ser/Thr) PKA substrate antibody; however, they did not identify the protein (16). In the present study, we confirmed the presence of a 270 kDa protein band in post-capacitation spermatozoa lysates.…”
Section: +supporting
confidence: 76%
“…Specifically, bicarbonate stimulates motility and hyperactivation through the activation of ADCY10 and tyrosine phosphorylation of AKAP3 in human spermatozoa [47]. Moreover, bicarbonate/ADCY10-induced protein phosphorylation is likely important in the cAMP signaling cascades that lead to hyperactivation in mouse [48] and bull spermatozoa [49].Based on the data obtained in the present study, we would like to emphasize that functional ADCY10 ortholog proteins exist in the heads of boar ejaculated spermatozoa. This fact enables us to account for the effects of bicarbonate on the fertilization-related events in the boar sperm heads.…”
supporting
confidence: 53%
“…However, there are only limited data regarding cAMP-dependent Ser/Thr phosphorylation in sperm proteins (chum salmon [42], boar [43,44], sea urchin [45], human [46] and mouse [47]). In this study, incubation with cBiMPS (0.1 mM) induced Ser/Thr phosphorylation of the sperm flagellar proteins, including the >250-kDa, 170-kDa, 155-kDa, 140-kDa and 42-kDa substrate proteins of AGC family kinases (Fig.…”
Section: Relationship Between Protein Phosphorylation and Calyculin Amentioning
confidence: 99%
“…1). One phosphorylated protein with a higher molecular mass than 250 kDa corresponds to the mouse sperm p270 protein that is quickly phosphorylated in response to bicarbonate and may be involved in the initial signaling events leading to activation and subsequent hyperactivation of flagellar movement [47]. Moreover, a major cBiMPS-dependent tyrosine-phosphorylated protein (estimated molecular mass: 70 kDa, Fig.…”
Section: Relationship Between Protein Phosphorylation and Calyculin Amentioning
confidence: 99%
See 1 more Smart Citation